Joint water purification from iron and manganese compounds by microfiltration ceramic membrane made of clay minerals - Dulneva, T.Yu. (Reports of the National Academy of Sciences of Ukraine, 2019)
The high efficiency of the process of joint water purification from Fe(ІІІ) and Mn(ІІ) compounds modified by them in the dynamic mode by a microfiltration ceramic membrane made of clay minerals is shown, and the steric mechanism of its action based on the difference in the pore sizes of the membrane and particles of Fe(ІІІ) and Mn(ІІ) compounds is justified. It has been established that such modification increased the retention capacity of the ceramic membrane to Mn(II) compounds. The influence of various technological factors on the characteristics of this process is studied. The negative effect of chlorides on the retention capacity of such modified membrane and a levelling role in this process of self-forming DM has been revealed. It has been established that the simultaneous purification of water from Fe(III) and Mn(III) compounds to their MPC in drinking water is expedient at the initial concentration of Fe(ІІІ) and Mn(ІІ), respectively, up to 42.3 and 4.0 mg/dm3, pH 8.3—8.4, operating pressure of 1.0 MPa, and a duration of the experiment of 120 min.